A novel dental adhesive containing Ag/polydopamine-modified HA fillers with both antibacterial and mineralization properties. (August 2021) - Zhang, Jiahui; He, Xi; Yu, Shiyang; Zhu, Jiufu; Wang, Huimin; Tian, Zilu; Zhu, Song; Cui, Zhanchen
Abstract: Objectives: To evaluate the antibacterial and mineralization properties of a dental adhesive containing Ag/polydopamine-modified HA (HA, hydroxyapatite) fillers. Methods: First, an HA-polydopamine-Ag-polydopamine (HA-PDA-Ag-PDA) filler was prepared and characterized using SEM, TEM, XPS, XRD and FTIR. Then, the HA-PDA-Ag-PDA filler was mixed into an adhesive at different mass fractions (0 wt%, 0.5 wt%, 1 wt%, 2 wt%) to prepare a functional adhesive. Antibacterial and mineralization tests were carried out, and the cytotoxicity of the functional adhesive against L929 fibroblasts was also examined. Results: The SEM, TEM, XPS, XRD and FTIR characterizations confirmed the successful preparation of the HA-PDA-Ag filler. The 1 wt% and 2 wt% functional adhesives showed the strongest bacterial inhibition effect among all the samples (p < 0.05). Obvious apatite crystals were observed in the SEM micrograph of the surface of the functional adhesive sample after immersion in artificial saliva for predetermined times (1 d, 7 d, 14 d and 28 d). There was no significant difference between the experimental group and the control group in terms of cell proliferation activity (p > 0.05). Conclusions: The 1 wt% and 2 wt% functional adhesives demonstrated good antibacterial and mineralization properties, as well as good biocompatibility. Clinical significance: Functional adhesives containing Ag/polydopamine-modified HA fillers with antibacterial and mineralization capabilities might have excellent potential to enhance the stability and durability of hybrid layers and prolong the service life of dental restorations. Our study on bifunctional adhesives has paved the way for future clinical applications to increase restoration longevity. Graphical abstract: Image, graphical abstract